Staircase at Bob Bungalow - Mumbai Archive Project Team (Jio Institute, 2024)
Mazagon features a mix of residential, commercial, and industrial structures that have changed ownership multiple times. Buildings have been remodelled and repurposed depending on their usage. For example, Bob Bungalow was built as a hospital but is now used as a residential building. As one enters through the arched entrance, a grand staircase welcomes visitors. The current tenants live in units arranged on either side of the corridor.